EFEKTIVITAS MODEL PEMBELAJRAN TGT (TEAM GAME TOURNAMEN) DALAM MENNGKATKAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM KELAS IV SDIT INSAN ROBBANI - Lamudin; Bahari; M. Makhrus Ali; Siti Afifatun; Meilisa Sajdah (Program Studi Manajemen Pendidikan Islam, 2023)
The problem of education in Indonesia is very complex, lately it has been very concerning, many factors there are internal factors and there are external factors that affect the learning outcomes of students, factors from within can be that children who are lazy to study can also lack interest in the subject, while factors from outside the environment that are less supportive and so on so that student learning outcomes have not been maximized, After conducting research using the TGT (team Game Tuornamen) learning model, the learning outcomes of SDIT Insan Robbani students increased and were very good, in this case the researcher used experimental quantitative research methods, Researchers will make comparisons in the same class after applying the TGT (Team Game Tournament) learning model, students' learning outcomes will increase, so researchers can conclude that after students are treated by applying the TGT learning model (Team Game Tournament, the learning outcomes of SDIT class IV students increase)